The politics of structural reforms: social and industrial policy change in Italy and Japan (Cheltenham, 2013)
"For countries undertaking economic or political reform the case of Italy and Japan is both highly instructive and sobering. The Politics of Structural Reforms reveals what Italy and Japan gained and lost through a series of social and industrial reforms in the 1990s and 2000s, and why the changes they made in their policies have had little impact in softening the recent economic crisis. Italy and Japan achieved miraculous economic growth in the postwar period. While their financial and manufacturing sectors cooperated in achieving international competitiveness, their political systems grew alike. The weaknesses of both economic and political compacts became apparent at the beginning of the 1990s, when the two countries were caught in an economic slump and fell into a stalemate that lasts to the current day. Since the early 1990's they have undergone a series of structural reforms, and momentous changes in their political systems. Through a detailed comparative analysis of the reforms of both countries in areas such as corporate governance, the labour market, social policy, and in their electoral systems the authors explain why these reforms have not resulted in economic and political success This innovative volume will be an excellent resource for political scientists specialized in political economy and industrial relations, labour economists and sociologists as well as policy practitioners and corporate governance specialists. Moreover, it is an enjoyable and informative read for all scholars and those interested in social and political reform."